2004
DOI: 10.1108/13632540410807673
|View full text |Cite
|
Sign up to set email alerts
|

Multinational corporations and public relations in a historically resistant host culture

Abstract: Since the onset of globalisation, many multinational corporations (MNCs) have been increasingly opening up subsidiaries in several host nations. While the entry of MNCs in some nations has been generally unproblematic, that has not been the case in every host nation. Fears of neocolonialism and postcolonial anxieties are very real phenomena in many parts of the world. When it comes to such resistant environments, MNCs need to be especially careful in how they conduct their public relations activities. This qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…If we are to truly study global practice, however, we need to be inclusive of eastern thought, the worldviews of indigenous peoples, and other cultural perspectives. Bardhan (2003;Bardhan and Patwardhan, 2004) makes this argument in her work on public relations practices in India; theory to guide practice differs in many ways that are not transferable when developed from within a paradigm consonant with the host culture. Chung and Ho (2009) provide an Eastern paradigm using the I-Ching, which informs Taoist, Buddhist and Confucianist thought, and the notion of chi/qi/ki, the basic life force or energy.…”
Section: Ramifications and Incommensurabilitiesmentioning
confidence: 99%
“…If we are to truly study global practice, however, we need to be inclusive of eastern thought, the worldviews of indigenous peoples, and other cultural perspectives. Bardhan (2003;Bardhan and Patwardhan, 2004) makes this argument in her work on public relations practices in India; theory to guide practice differs in many ways that are not transferable when developed from within a paradigm consonant with the host culture. Chung and Ho (2009) provide an Eastern paradigm using the I-Ching, which informs Taoist, Buddhist and Confucianist thought, and the notion of chi/qi/ki, the basic life force or energy.…”
Section: Ramifications and Incommensurabilitiesmentioning
confidence: 99%
“…The list of researchers who have incorporated the GrunigHunt model into their international research is substantial: B. Lee (2004), Bardhan (2003), Huang (2001), Kim and Hong (1998), Grunig et al (1995), Culbertson (1996), Chen (1996), Ekachai and Komolsevin (1996), , Alanazi (1996), González and Akel (1996), Freitag (2004), and Ogbondah and Amiso (2004), to name several prominent examples, have tested international public relations waters using the Grunig-Hunt model.…”
Section: Chapter Goalsmentioning
confidence: 99%
“…S. Sivakumar, the Division's chief executive, decided to use technology to aid farmers who were struggling to grow food to eat plus a crop to sell. These farmers lacked irrigation and other resources, and knew little about even Bardhan and Patwardhan (2003), two Indian-born scholars teaching in the United States, examined multinational corporations Lever and Suzuki and found that it is possible for major companies to establish a presence successfully in India despite the country's fears of neocolonialism, provided that they respect the culture and perform in a socially responsible manner. They say that India's fairly recent independence means that there is a lingering fear of "cultural and economic imperialism".…”
Section: South and Southeast Asia 125mentioning
confidence: 99%
See 1 more Smart Citation
“…With every new privatisation measure "arguments of neocolonialism, cultural imperialism and economic exploitation [surge] afresh" (Ref. 44). The Dabhol/Enron case also demonstrated the potential impacts of international investment laws for India since it led to legal suits.…”
Section: Private Investmentmentioning
confidence: 99%